CONSUMPTION VOLUMES TECHNOLOGY OF ELECTRICITY AND HEAT BY DEPARTMENTS OF THE UNIVERSITY - Pshinko, O. M.; Kuznetsov, V. G.; Shaptala, M. V.; Shaptala, D. E. (Science and Transport Progress, 2015)
Purpose. Efficient use of natural energy resources is one of the priorities of the state policy in the sphere of universities and institutions of the Ministry of Education and Science of Ukraine. Besides search and development the new efficient and clean energy systems it is necessary to implement optimal management of the development and operation of existing facilities, reducing their energy costs. Purpose of this work is to develop consumption volume technology of electricity and heat by scientific departments of Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan (DNURT) for further finding the ways to reduce energy consumption. The problem is due to the specifics of University’s energy scheme. There is a difficulty for the installation of energy meters and data acquisition about their use in individual branches and structural units. At the same time it is impossible to assess qualitatively the energy position of scientific departments. Methodology. The method to determine the electricity and heat consumption for space heating of scientific departments at the university is based on «The intersectoral rules of electricity and heat energy for institutions and public sector organizations in Ukraine» and «Codes and regulations on rationing of fuel and heat energy for heating the residential buildings as well as for economic needs in Ukraine». Findings. Developed determining expenditure technology of electricity and heat for heating by scientific departments at the DNURT named after Academician V. Lazaryan allows obtaining data on energy consumption in individual units without direct measure and analyzing the effectiveness of energy saving technologies. Originality. It is represented by energy costs in the form of two components and these components are defined on the basis of the energy audit. This enables the energy inputs to implement energy efficiency measures in the research departments of the university. Practical value. The developed method can be used as practical tools to monitor energy consumption in the above mentioned university and in similar facilities.